2018
DOI: 10.3390/w10111688
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Use of Satellite-Based Estimates and High-Resolution Precipitation Datasets for the Study of Extreme Precipitation Events over the Iberian Peninsula

Abstract: An assessment of daily accumulated precipitation during extreme precipitation events (EPEs) occurring over the period 2000–2008 in the Iberian Peninsula (IP) is presented. Different sources for precipitation data, namely ERA-Interim and ERA5 reanalysis by the European Centre for Medium-Range Weather Forecast (ECMWF) and Tropical Rainfall Measuring Mission (TRMM) Multisatellite Precipitation Analysis (TMPA), both in near-real-time and post-real-time releases, are compared with the best ground-based high-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 53 publications
(107 reference statements)
3
13
0
Order By: Relevance
“…This was attributed to the precipitation inputs provided by the ERA5 dataset, which also failed to represent higher precipitation values as shown in Figure 3 for the Santiago meteorological station. This tendency was also verified by Hénin et al [66], who concluded that reanalysis products such as ERA5 present an underestimation of heavy precipitation events. Hence, the amount of water entering the basin during heavy rain events in that dataset was clearly below measured rainfall and proved to be insufficient for the model to reach higher flow peaks.…”
Section: Prediction Of River Flow In the Ulla River Watershedsupporting
confidence: 65%
“…This was attributed to the precipitation inputs provided by the ERA5 dataset, which also failed to represent higher precipitation values as shown in Figure 3 for the Santiago meteorological station. This tendency was also verified by Hénin et al [66], who concluded that reanalysis products such as ERA5 present an underestimation of heavy precipitation events. Hence, the amount of water entering the basin during heavy rain events in that dataset was clearly below measured rainfall and proved to be insufficient for the model to reach higher flow peaks.…”
Section: Prediction Of River Flow In the Ulla River Watershedsupporting
confidence: 65%
“…In this study, ERA5 reanalysis data are used instead, given the outcomes of Hénin et al . (2018) where different precipitation data sources were compared to IB02 on the IP and ERA5 accounted for the best accuracy metrics. Eventually, the ranking produced here covers the period 1979–2018 and daily accumulated precipitation is obtained as the sum of hourly values, as described in Section 2.1.…”
Section: Methodsmentioning
confidence: 99%
“…The ranking covers the period up to 2008 as it is based on IB02, the most comprehensive ground-based daily precipitation dataset available for the IP (Belo- Pereira et al, 2011;Herrera et al, 2012), whose records are not available for recent years. In this study, ERA5 reanalysis data are used instead, given the outcomes of Hénin et al (2018) where different precipitation data sources were compared to IB02 on the IP and ERA5 accounted for the best accuracy metrics. Eventually, the ranking produced here covers the period 1979-2018 and daily accumulated precipitation is obtained as the sum of hourly values, as described in Section 2.1.…”
Section: Precipitation and Wind Rankingmentioning
confidence: 99%
“…Although ERA5 precipitation was only released very recently, its improvement over ERA-Interim and other global precipitation datasets has attracted significant attention. Hénin et al [144] assessed the ability of ERA5, ERA-Interim, and TRMM 3B42RT and TRMM 3B42 to reflect daily extreme precipitation events over the Iberian Peninsula over the period [2000][2001][2002][2003][2004][2005][2006][2007][2008]. It was found that ERA5 reanalysis gave large improvements over ERA-Interim, and it also outperformed the two satellite-based datasets.…”
Section: Assessment and Comparisonmentioning
confidence: 99%